Pengaruh Permainan Keseimbangan Tubuh Terhadap Perkembangan Motorik Kasar Pada Anak Kelompok A di TK 02 Puntukrejo Ngargoyoso Karanganyar Tahun Pelajaran 2015/2016 - Wulansari, Yunita; S.H.,M.Pd, Dra. Surtikanti,S.H.,M.Pd (2016)
The purpose of this study is to determine the effect of body balance game against gross motor development of children in group A at TK 02 Puntukrejo Ngargoyoso Karanganyar Academic Year2015/2016. Methods in this study was a quantitative method using a kind of experimental research with pre-experimental design research design was one group pretest-posttest design. This study was conducted in 02 kindergartens Puntukrejo Ngargoyoso Karanganyar. Subjecs in this study was a group of children in kindergarten 02 Puntukrejo with the number of 22 children. Data collection techniques in this research was conducted through observation, that observation participate (participan observation). Data analysis techniques in this study used ttest with SPSS 16.0 for Windows. The results of data analysis using ttest obtained thitung - 11.224 ≤ -ttabel-2.080 so that H0 rejected and Ha accepted which means there were significant body balance game against gross motor development of children.